A study of the salary and hourly employees at Trane Company, La Crosse, Wisconsin, toward the value of participating in the company recreation program - Frawley, Joan (My University, 1982)
A random sample of participants in the Trane Company recreation program were selected from two groups, salary employees and hourly employees. A questionnaire was constructed and administered through the U.S. Mail to the samples of salary and hourly employees. This study traces the correlation between involvement in the recreation program and attitudes among employees involved in such programs.
Keywords: Industrial recreation --Wisconsin --La Crosse; Trane Company --Employees --Attitudes